2010
DOI: 10.1128/iai.00996-09
|View full text |Cite
|
Sign up to set email alerts
|

Opacity Proteins Increase Neisseria gonorrhoeae Fitness in the Female Genital Tract Due to a Factor under Ovarian Control

Abstract: The neisserial opacity (Opa) proteins are a family of antigenically distinct outer membrane proteins that undergo phase-variable expression. Opa ؉ variants of Neisseria gonorrhoeae strain FA1090 are selected in a cyclical pattern from the lower genital tract of estradiol-treated mice. Here we show that cyclical recovery of Opa ؉ gonococci does not occur in ovariectomized mice; therefore, the reproductive cycle plays a role in the selection kinetics in vivo. As predicted by the selection pattern shown by wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 59 publications
2
56
0
Order By: Relevance
“…OpaD is an Opa CEA protein that confers a strongly opaque phenotype on Gc colonies. OpaD expressors are isolated from the male urethra and mouse genital tract after infection with FA1090 Gc, and OpaD ϩ Gc stimulates a strong oxidative burst in PMNs (25,30,50,52,53) (Fig. 5A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…OpaD is an Opa CEA protein that confers a strongly opaque phenotype on Gc colonies. OpaD expressors are isolated from the male urethra and mouse genital tract after infection with FA1090 Gc, and OpaD ϩ Gc stimulates a strong oxidative burst in PMNs (25,30,50,52,53) (Fig. 5A).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, antibodies have been raised against individual FA1090 Opa proteins (23,24). Prior to this work, a derivative of FA1090 in which all 11 opa genes had been deleted, the ⌬opaA-K mutant, was constructed (50,53). However, the FA1090 ⌬opaA-K mutant has a significant growth defect on solid and in liquid media (53) (our unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these host restrictions, studying gonococcal pathogenesis in the murine model has yielded considerable insight into the host response to infection (25,31,58,76) and the role of certain gonococcal virulence factors in evasion of host defenses (34,75,81,84,85). The mouse model has also allowed the demonstration of hormonal (13,32,73), as well as the effect of certain antibiotic resistance mutations on microbial fitness (82). The increasing availability of transgenic mice in several of these host-restricted factors should allow for improved study of gonococcal chlamydial coinfection in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The host response and progression of infection and disease in mice infected with C. muridarum more closely mimics human disease, however, than does experimental infection of mice with C. trachomatis (3,16), and the C. muridarum mouse model is commonly used to examine the immunobiology of chlamydial genital infection. Host restrictions that prevent murine infection with N. gonorrhoeae from fully mimicking human infection include the absence of colonization receptors for pili and opacity (Opa) proteins (13,36,52,80) and differences in soluble complement regulatory proteins that bind the gonococcal surface to downregulate complement activation (54). N. gonorrhoeae also cannot use murine lactoferrin or transferrin as sources of iron (14,43), and the gonococcal immunoglobulin A1 (IgA1) protease cannot cleave mouse IgA (40).…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be strong in vivo selection for Opa expression in men, as bacteria isolated from men inoculated with phenotypically Opa-negative gonococci (bacteria derived from a single colony that fails to refract light) are usually Opa expressing (23,46). Cole et al (9), using a derivative of FA1090 that was genetically devoid of opa, showed previously that the expression of Opa increased gonococcal fitness in the female mouse genital tract due to a factor under ovarian control. Depending on the predominant opa allele expressed, gonococci are capable of interacting with a variety of epithelial cells (11,25,55) or human neutrophils (7,24).…”
mentioning
confidence: 99%